2022
DOI: 10.3390/biology11010077
|View full text |Cite
|
Sign up to set email alerts
|

ALS2-Related Motor Neuron Diseases: From Symptoms to Molecules

Abstract: Infantile-onset Ascending Hereditary Spastic Paralysis, Juvenile Primary Lateral Sclerosis and Juvenile Amyotrophic Lateral Sclerosis are all motor neuron diseases related to mutations on the ALS2 gene, encoding for a 1657 amino acids protein named Alsin. This ~185 kDa multi-domain protein is ubiquitously expressed in various human tissues, mostly in the brain and the spinal cord. Several investigations have indicated how mutations within Alsin’s structured domains may be responsible for the alteration of Alsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 82 publications
(238 reference statements)
1
12
0
Order By: Relevance
“…It was demonstrated that mutant alsin molecules with in‐frame deletions existed as abnormally higher molecular weight complexes 14 . All our variants were detected in a homozygous state similar to the majority of the reports 2 that highlighted the significant effect of consanguinity on disease origination.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It was demonstrated that mutant alsin molecules with in‐frame deletions existed as abnormally higher molecular weight complexes 14 . All our variants were detected in a homozygous state similar to the majority of the reports 2 that highlighted the significant effect of consanguinity on disease origination.…”
Section: Discussionsupporting
confidence: 84%
“…NCV and EMG were normal for all patients, as a distinguishable sign between IAHSP/JPLS and JALS 1 . It is noteworthy that the frequency of disease clinical and neuroimaging features are currently underestimated in the literature due to paucity of published cases, without full clinical details in most 2,10 . It has been reported that cognitive function is preserved in ALS2 ‐related disorders 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology and pathogenesis of ALS are not fully understood, research has shown that inflammatory responses in the peripheral and central nervous systems contribute to the injury of motor neurons and promote disease progression. The pathological processes of ALS2 involve endoplasmic reticulum stress, oxidative stress, neuroinflammation, and axonal transport dysfunction, and the study of the relationship between the structure and function of the ALS2 protein and the study of interacting proteins or chaperones will provide novel insights into the molecular pathogenesis of ALS ( 122 ) ( Figure 8 ).…”
Section: Uxt and Neurodegenerative Diseasesmentioning
confidence: 99%
“…The CHMP2B protein is an essential component of the ESCRT III complex, which is part of the machinery for MVB and EV formation, as discussed above [ 58 ]. C9orf72 , VAPB , FIG4 , SPG11 and ALS2 encode proteins which are involved in intracellular trafficking of vesicles [ 59 , 60 , 61 , 62 , 63 , 64 ]. Optineurin and SQSTM1/p62 proteins are both autophagy receptors and are activated through phosphorylation by TBK1 [ 65 ].…”
Section: Evs In Alsmentioning
confidence: 99%